PENAMBAHANMINYAK ATSIRI RIMPANG JERINGAU (Acorus calamus L.) SEBAGAI ANTIBAKTERI TERHADAP KARAKTERISTIK SENSORI SABUN TRANSPARAN - Bambang Sisto Nadi; Dewi Fortuna Ayu; Akhyar Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was to get the sensory characteristicon transparent soap with the addition of essential oil from jeringau rhizome.The research used a Complete Randomized Design with five treatments and three replications. The treatments were addition of essential oils in consecutive S0 (0 ml), S1 (0,05 ml), S2(0,10 ml), S3 (0,15 ml), and S4 (0,20) ml in 100 ml of transparent soap formula. The data were statistically analyzed using Analysis of Variance and Duncanʹs New Multiple Range Test at 5%. The research showed that addition of jeringau essential oils significantly effected on descriptive test, and hedonic test. Transparent soap elected from this research was treatment S4 (addition essential oils 0,20 ml). The result of descriptive test on transparent soap showed that the soap had jeringau flavor and assessment of hedonic test on transparent soap was favored by the panelists. Keywords:Jeringau, essential oil, transparent soap, antibacterial.